Performance of PSMA PET for Staging of Prostate Cancer - Guner, A.; Unal, K.; Temiz, H.; Kaya, E.; Vardareli, E.; Tuna, M.; Doganca, T. (SPRINGER, 2019)
32nd Annual Congress of the European-Association-of-Nuclear-Medicine (EANM), Barcelona, SPAIN, OCT 12-16, 2019